The Relationship between Conflicts, Economic Shocks, and Death with Depression, Economic Activities, and Human Capital Investment in Nigeria - Jamison, Julian (World Bank, Washington, DC, 2018)
This paper examines the links between adverse events, depression, and decision making in Nigeria. It investigates how events such as conflicts, shocks, and deaths can affect short-term perceptions of welfare, as well as longer term decisions on economic activities and human capital investments. First, the findings show that exposure to conflict has the largest and strongest relationship with depression, associated with a 15.3 percentage point increase in the probability of reporting depressive symptoms (from a base of 22 percent). This is equivalent to a reduction in annual per capita income of around US$52 (in present day terms). Second, the study randomized the timing of the module on adverse events with respect to the mental health module. The analysis finds that individuals who were reminded about their history of adverse events (provided that they had one) have a 6.5 percentage point higher probability of reporting depressive symptoms. The final sets of results show that depression is associated with lower labor force participation and child educational investment. People with depressive symptoms are 8 percentage points less likely to work; this is driven by a reduction in engagement in agricultural activities for men and self-employment for women. In addition, households with a parent exhibiting depressive symptoms spend 20 percentage points less on education. These results suggest that there is a direct link between mental health, welfare perceptions, and decision making, beyond the indirect link via exposure to adverse effects.